Inflammatory markers predict efficacy of immunotherapy in advanced non-small cell lung cancer: a preliminary exploratory study - Yingqing Zhang; Na Yan; Yan Feng; Yonglei Wu; Yuejiao Sun; Xixi Gao; Chao Gu; Xiaolong Ma; Feng Gao; Hui Zhang; Jiaqi Zhou (Discover Oncology)
Abstract Objective The purpose of this study is to analyze the predictive value of neutrophil to lymphocyte ratio (NLR), lymphocyte count to monocyte count ratio (LMR), platelet to lymphocyte ratio (PLR), platelet count multiplied by neutrophil count to lymphocyte count ratio (SII), red blood cell distribution width (RDW), packed cell volume (PCV), and plateletcrit (PCT) levels in advanced non-small cell lung cancer (NSCLC) patients treated with PD-1/PD-L1 inhibitors. Materials and methods From March 2019 to August 2023, we screened 104 of 153 patients with stage III unresectable local advanced NSCLC and IV NSCLC who received PD-1/PD-L1 inhibitor therapy at our hospital and met the inclusion and exclusion criteria for analysis. All patients were collected for clinical information, including baseline blood indicator (NLR, PLR, LMR, SII, CRP, RDW, PCV and PCT) levels before PD-1/PD-L1 inhibitor therapy and blood indicator levels and imaging evaluation results every two cycles after PD-1/PD-L1 inhibitor therapy. We analyzed the predicted impact of baseline blood indicators on PD-1/PD-L1 inhibitor treatment response, the discriminatory power of blood indicators on treatment response after efficacy evaluation, and the dynamic changes in blood indicators during PD-1/PD-L1 inhibitor treatment. Results In our study data, baseline levels of NLR, PLR, LMR, SII, CRP, RDW, PCV, and PCT did not provide good predictive identification of PD-1/PD-L1 inhibitor primary resistance and effective treatment response populations. These indicators showed no significant distribution differences in Mann Whitney Wilcoxon analysis, univariate and multivariate logistic regression analysis between the primary resistance group and the effective treatment response group. We validated the NLR threshold of 5 from multiple previous studies in the data of this study, and patients with NLR > 5 also did not show a significant tendency towards the primary resistance group. The levels of NLR, PLR, LMR, SII, CRP, RDW, PCV, and PCT after efficacy evaluation also cannot effectively distinguish primary drug resistance and effective treatment response populations. However, in the longitudinal data analysis before and after PD-1/PD-L1 inhibitor treatment, we found that the NLR, SII, and CRP levels of patients who responded effectively were significantly reduced compared to baseline status. But this phenomenon was not observed in PD patients. Conclusions PD-1/PD-L1 inhibitors treatment significantly altered the levels of NLR, SII, and CRP in patients with advanced NSCLC. Dynamic monitoring of NLR, SII, and CRP levels may have potential application value in monitoring the therapeutic efficacy of ICIs. In our study, the baseline status of blood indicator levels did not achieve good primary drug resistant patient identification. The potential value of blood indicators in predicting primary resistance to ICI should be further explored in larger research cohorts.